Effekte der Seelsorgeausbildung Ehrenamtlicher - Dinger, Ulrike; Rek, Isabelle (Pastoraltheologie, 2017)
Approx. 250 volunteers responded to questionnaires at the beginning of their intensive training for this telephone service; this was repeated after six months, and again after the completion of the training. Psychotherapy research has shown that personal factors of the therapist and interactive factors play an important role for a better outcome. For the current study, data on volunteers' personal change during training as well as the prediction of their competence experience after training completion is presented. Factors and the interpersonal experiences during the training sessions contribute to a better experience of competence in the first telephone conversations.